Analisis dan Perancangan Sistem Informasi Produksi - Lea Sulaiman Saputra (Bina Nusantara University, 2010)
The objective of this research is to help solve problems faced by some companies in production planning and controlling so it could run well and effective. The research method used is literature study, field research and interview. Good internal controlling will help increasing production. The company does not have internal auditor section that will check separately company’s events and internal controlling system.